Efektivitas Inquiry Training Berbasis Kearifan Lokal Terhadap Keterampilan Berpikir Kreatif dalam Pembelajaran IPA - Sekarsari Putri, Agnesi; Rizky Wirawan, Pradita; Cinthya Habellia, Ray (Journal of Primary Education Research, 2025)
The creative thinking skills of Indonesian students are still relatively low, even though this is one of the important skills that need to be developed so that students can compete and succeed in facing the challenges of the 21st century. This study aims to improve students' creative thinking skills through the use of inquiry training based on local wisdom. This is a quasi-experimental study using a pretest-posttest nonequivalent control group design. The sample consisted of 60 students from the experimental and control classes, selected using cluster random sampling because the sample was drawn from class groups. The instrument was a creative thinking skills test consisting of five items. The questions were analyzed using an Independent Sample T-Test with SPSS 22. The results showed that the inquiry training model integrated with local wisdom could improve students' creative thinking skills to a high level. The improvement in creative thinking skills in the experimental class was higher than in the control class. Additionally, there was a difference in students' creative thinking skills between the experimental class and the control class. Inquiry training based on local wisdom can be an alternative for teachers to address the issue of underdeveloped creative thinking skills in students.